A Review on the Machinability Characteristic of Stainless steel in various machining operations - Vineet Dubey; C.K. Dixit (AG Volumes, 2022)
Austenitic stainless steels are one the most adaptable grade in stainless steel and are widely employed in a variety of sectors. It possesses a high level of durability, ductility, toughness at cryogenic temperatures, and corrosion resistance. Despite the fact that austenitic stainless steels are the most widely utilized of the five stainless steel families and have excellent ductility, endurance, and resistance to corrosion, they do have some drawbacks that operate as stumbling blocks in some applications. Because of the diverse nature of stainless steels, it is tough to put their machinability in concrete terms. One of the most broadly adopted materials is austenitic stainless steel., accounting for 10% of global manufacturing of steel, with austenitic steels accounting for 70% of total stainless steels. According to data from the ISSF, global stainless steel output has been steadily increasing, and consumption is predicted to continue to rise each year. The current study briefly introduces some key ideas in austenitic stainless steel metallurgy, as well as some of the issues surrounding austenitic stainless steel machining. A review of the numerous works of researchers in this field is also included. Finally, a discussion of prospective research fields concludes this work.